Bioremendiation of colour contaminant for textile wastewater - Muda, Khalida (Faculty of Civil Engineering, 2007)
Degradation process of wastewater through biological treatment approaches offer great advantages over physical and chemical treatment process. Biological treatment using aerobic granular sludge in sequential batch reactor has become a novel application particularly for the treatment of industrial and municipal wastewater. However many factors that are believed to influence the development of aerobic granules are not yet clear especially related to the treatment of textile wastewater. In this study, identified specialised dye degrader microbes was integrated in the development of aerobic granules which will later be used for the treatment of textile wastewater. This study is still in the progress of developing the aerobic granules. This report presents the progress of work that has been conducted up to today.